Algorithm for Dynamic Reactive Power Optimization of Regional Power Grid Based on Interior Point Method and Neighborhood Search Decoupling Dynamic Programming Method - Jie ZHANG; Hengfeng WANG; Shengchun LIU; Huabiao WANG; Canghai WANG; Yao RAN; Xianmin WANG; Yongfei MA; Wei YAN (Zhongguo dianli)
The dynamic programming method can efficiently and accurately solve the dynamic reactive power optimization problem of the small-scale regional power grid. However, with the power grid scale increment, the optimization problem would have the combination explosion issue, which would lead to the rapid growth of solution time. Therefore, a two-stage hybrid dynamic reactive power optimization method based on the interior point method and the neighborhood search decoupling dynamic programming method is proposed. In the first stage, Sigmoid function is used to achieve the continuity of the original model, and then the interior point method is adopted to find the continuous optimal solution; while in the second stage, on the basis of the continuous solution, the heuristic neighborhood search strategy is employed to determine the search space of the decoupling dynamic programming method. The regional power grid dynamic reactive power optimization problem is solved through the decoupling between stations, the decoupled coordination of voltage regulation and reactive power compensation equipment, and the dynamic programming within the stations. The two-stage method could not only ensure the quality of the optimal solution, but also avoid solving the state combination explosion problem with discrete variables, which greatly improves the computational efficiency. The effectiveness of the proposed method is verified by the simulations on a 220 kV control zone.